For this case we have the following equation:
[tex]I = \frac {nE} {nr + R}[/tex]
We must clear the variable "n", for them we follow the steps below:
We multiply by [tex]nr + R[/tex] on both sides of the equation:
[tex]I (nr + R) = nE[/tex]
We apply distributive property on the left side of the equation:
[tex]Inr + IR = nE[/tex]
Subtracting [tex]nE[/tex] from both sides of the equation:
[tex]Inr-nE + IR = 0[/tex]
Subtracting IR from both sides of the equation:
[tex]Inr-nE = -IR[/tex]
We take common factor n from the left side of the equation:
[tex]n (Ir-E) = - IR[/tex]
We divide between Ir-E on both sides of the equation:
[tex]n = - \frac {IR} {Ir-E}[/tex]
Answer:
[tex]n = - \frac {IR} {Ir-E}[/tex]